Italy : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper analyzes the conditions under which Italian banks can earn sufficient profits to grow out of their asset quality problems, rebuild capital buffers, and finance the real economy. A bottom-up analysis of the 15 largest Italian banks suggests that restoring sustainable profitability depends heavily on the growth outlook. Many banks are expected to become more profitable as the economy recovers, but their capacity to lend depends on the size of their capital buffers. However, a number of smaller banks face substantial profitability pressures, highlighting the need to reduce the large stock of nonperforming loans and for further cost cutting and efficiency gains.